Mimesis and empire : the new world, Islam, and European identities - Fuchs, Barbara, 1970- (Cambridge studies in Renaissance literature and culture, 2001)
Explores the dynamics of imitation among early modern European powers in literary and historiographical texts from sixteenth- and early seventeenth-century Spain, Italy, England, and the New World. The author considers problems of reading and literary transmission; imperial ideology and colonial identities; counterfeits and forgery; and piracy.